Conversion of bio-coke from Spirulina platensis microalgae as an alternative sustainable energy - Nur Syahirah Kamal Baharin; Yoshinobu Ikeda; Ken Moizumi; Tamio Ida (Case Studies in Chemical and Environmental Engineering, 2024)
This study aimed to investigate the potential of Spirulina platensis (SP), a high protein content microalgae species, to be used as feedstock for a new type of solid biofuel technology, namely bio-coke. The SP bio-coke production was conducted at different formation temperatures of 130, 150 and 170 °C without any binder. The results showed that SP BIC 150, which was produced at the optimum formation temperature of 150 °C, exhibited the highest density and mechanical strength when compared with that of SP BIC 130 and SP BIC 170. This means that it strongly influenced its stable structure during the combustion process. With the strong structure of SP BIC 150, the breakdown of bio-coke can be prevented during flame combustion, thereby contributing to a longer char and total combustion time. The conversion of SP microalgae showed good potential to be used as an alternative renewable energy source in the future.